The effect of pentoxifylline drug on bax/bcl2 gene dosage expression changes following ischemic reperfusion injury in kidney - Hashemi, Mehrdad (Archives of Advances in Biosciences, 2015)
Global cerebral ischemia (GCI) and reperfusion induced apoptosis that lead to cell injury and death. The bax and bcl-2 are pro-apoptotic and anti-apoptotic genes, respectively. These genes belong to The B-cell lymphoma-2 (bcl-2) family.In this study; we assessed the effect of pentoxifylline drug on bax/bcl2 gene dosage expression changes following ischemic reperfusion injury in kidney. In this experimental study, 20 male wistar rats were accidently divided them on two tenth group of control and treatment groups. In the control group, celiotomy was performed by ventral midline incision. The left kidney was isolated, and then both the renal artery and vein were obstructed. After 60 minutes of warm ischemia, vessel obstruction resolved and the right kidney was removed. 72 hours after reperfusion, tissue samples were taken from left kidney for histopathology. All these steps in treatment group were exactly repeated after administration of 45 mg/kg/PO pentoxifylline (3 hours before operation) and in this group treatment was continued every 12h until 3 days. In this research quantitative real-timePCR is used for the detection expression Bcl2 and Bax genes in ischemia group and PNT drug group and compared to normal sample. The results showed the gene dosage ratio of Bax/bcl2 in PNT group decline than to ischemia group. Therefore, the pentoxyfylline might have a role in control of apoptosis result from Ischemia- reperfusion